Plant Vacuolar Processing Enzymes - Vorster, Barend Juan; Cullis, Christopher A.; Kunert, Karl J. (Frontiers in Plant Science, 2019)
Plant proteomes contain hundreds of proteases divided into different families based on evolutionary and functional relationship. In particular, plant cysteine proteases of the C1 (papain-like) and C13 (legumain-like) families play key roles in many physiological processes. The legumain-like proteases, also called vacuolar processing enzymes (VPEs) perform a multifunctional role in different plant organs and during different stages of plant development and death. VPEs are similar to animal caspases, and although caspase activity was identified in plants almost 40 years ago, there still remains much research to be done to gain a complete understanding of their various roles and functions in plants. Here we summarise not only the current existing knowledge on plant VPEs, including recent developments in the field, but also highlighting future prospective areas to be investigated to obtain a more detailed understanding on the role of VPEs in plants.